a) Unless part of the problem has been cut off you didn't need to take a derivative. Just plug in the values as I showed you.
d) y = f(x^2-3)
y' = f'(x^2-3)*2x
e) k(x) = f(x^2)/f(x)
Use the quotient rule:
k'(x) = [f'(x^2)*2x*f(x) - f(x^2)*f'(x)]/[f(x)]^2
The others look fine.
I noted that most of the mistakes are due to an improper application of the composition rule:
y = f(g(x)) => y' = f'(g(x))*g'(x)
Make sure when you take the derivative of the "outer" function, f, you keep the same argument g(x) as you had in the original part of the problem.